Measure of body composition by MOC DEXA, in children and teenagers with eating disorders - Tagliabue, Luca; Maioli, Claudio; Bonini, Marita; Giacchero, Roberta (Progress in Nutrition, 2018)
Introduction: Feeding has various characteristics and parameters including preferences of certain foods and eating habits, meal profile, regulation of the sense of hunger and satiety. In nutrition disorders (DCA) we find a constant alteration in the relationship between food and the individual with tendencies to hyper nutrition or as opposed to hypo nutrition. This can lead to the medium and long term compromising physical health and/or social psychic relationships. Aim: The aim of the study was to retrospectively examine a group of patients with DCA in order to analyze and characterize patients regarding their body composition, evaluated by MOC-DEXA, anthropometric parameters and hematochemical parameters. Materials and methods: The study included 28 patients (26 females and 2 males) of mean age of 13.6 years. The following parameters were analyzed for each patient: date of birth, origin, age at diagnosis, anthropometric parameters (weight, height, BMI), amenorrhea, quantification of physical activity, dose of 25(OH) vitamin D, MOC total body, left femoral muscle MOC, spine MOC and therapeutic pathway. Data was processed using excel programs and statistical analysis was performed using SPSS 15.0 for windows. Results: The sample examined shows that the starting age in about 50% of cases is between 13 and 14 years. The average height of patients was 156.1 cm, weight 43.8 kg and BMI of 17.8 kg/m2. Physical activity averaged 4.64 hours/week. Dosage of 25(OH) vitamin D was 25.4 ng/ml, while the therapeutic route consisted in the integration of dietary-nutritional, psychotherapeutic and pharmacological treatments. Discussion and Conclusions: The results of our study show that the severity of the disease correlates well with early onset. Our study shows that there are no menstruating patients with a weight below 43 kg, regardless of age and height. The weight t of 43 kg seems to be a true indicator to discriminate if there is or not amenorrhea. A further study with more patients is therefore necessary to confirm the data which, however, already well correlates with the clinical status of the patients.